Resolution Frameworks for Islamic Banks - Awadzi, Elsie Addo (IMF Working Papers; Working Paper ;, 2015)
Islamic banking is growing rapidly and its potential impact on global financial stability cannot be underestimated. International standards for resolving banks have evolved after the global financial crisis, culminating in the Financial Stability Board's ('FSB') Key Attributes of Effective Resolution Regimes for Financial Institutions. This paper examines the applicability of the Key Attributes to the resolution of Islamic banks. It concludes that a number of issues would need to be addressed, owing to Islamic banks' unique governance structures and balance sheets. It recommends international guidance for the design of robust Shari`ah -compliant resolution frameworks for jurisdictions with Islamic banks.